Las Teorías de Enseñanza y los Estilos de Aprendizaje y los Modelos Teóricos para ajustarlos / Teaching Theories, Learning Styles and Theoretical Models for their Adjustment - Pacheco Rios, Rosana (Revista Internacional de Aprendizaje en la Educación Superior, 2019)
ABSTRACT In this research article we present the characterization of the Teaching Theories of 59 professors and Learning Styles of 666 students of the School of Sports Organization of the Autonomous University of Nuevo Le.n, and the design of three Theoretical Models, product of the statistical analyses of socio-demographic, academic, and contextual variables of two validated questionnaires. The Theoretical Models present information regarding the aspects to consider for the adjustment of Teaching Theories with Learning Styles and to propose Institutional, School, and Curricular Reforms and Family Strategies. RESUMEN En este artículo se presenta la caracterización de las Teorías de Enseñanza de 59 profesores y los Estilos de Aprendizaje de 666 estudiantes de la Facultad de Organización Deportiva de la Universidad Autónoma de Nuevo León, y el diseño de tres Modelos Teóricos producto del análisis estadístico de las variables socio-demográficas, académicas y contextuales de dos cuestionarios validados. Los modelos presentan información sobre los aspectos a considerar para ajustar las Teorías de Enseñanza con los Estilos de Aprendizaje y para proponer Reformas Institucionales, Escolares, Curriculares y Estrategias Familiares.